Efficacy of cognitive behavioural therapy for internet gaming disorder. (22nd January 2020) - Han, Jiwon; Seo, Yesul; Hwang, Hyunchan; Kim, Sun Mi; Han, Doug Hyun
Abstract: Cognitive behavioural therapy (CBT) is considered to be an effective treatment for internet gaming disorder (IGD). This study examined the effectiveness of CBT in treating impulsivity, anxiety, avoidance, and family and environmental problems in patients. A total of 101 patients completed the CBT programme, and 104 completed the supportive therapy. The CBT programme consisted of fourteen 90‐min sessions with one therapist and four to five patients, once or twice a week. The supportive therapy group visited a psychiatric outpatient department once or twice a week until they completed 14 visits. Outcomes were measured in terms of improvement in IGD, psychological symptoms, and social interaction. The CBT group (improvement: 67 [66.3%] versus non‐improvement: 34 [33.7%]) showed more improvement in IGD compared with the supportive therapy group. The CBT group also showed a greater decrease in internet addiction, anxiety, impulsivity, and social avoidance. In the CBT group, among patients who improved, the greatest improvements were in internet addiction, attention, depression, anxiety, impulsivity, social avoidance, and family cohesion. Our CBT programme may be more effective than supportive therapy with regard to improvement in IGD symptoms by controlling anxiety, impulsivity, and social avoidance. In addition, CBT‐related improvements in patients with IGD could be enhanced by controlling anxiety, social avoidance, and family cohesion.